A molecular design approach towards elastic and multifunctional polymer electronics - Yu Zheng (Nature Portfolio, 2021)
Next-generation skin-inspired electronics require enhanced mechanical robustness and device complexity including elasticity, solvent resistance, and facile patternability. Here, the authors show a molecular design concept that simultaneously achieves all these requirements by covalently linking an in-situ formed rubber matrix with polymer electronic materials.